Epidemiology of lymphatic filariasis in Nilphamari district, Bangladesh - Anik, Md Khalid Eakbal; Khanum, Hamida; Rizvi, Iftekhar Ahmed; Alam, Shahela; Banu, Hasina (Dhaka University Journal of Biological Sciences, 2016)
The present study was carried out in Filaria Hospital of Nilphamari to find out the current status of lymphatic filariasis (LF) in Nilphamari district: An endemic area for lymphatic filariasis in Bangladesh. The inhabitants of the villages, the outdoor patients and hospitalized patients in Filaria Hospital were selected for the study. The current status and the prevalence of filariasis in Nilphamari district was 4.43%, in Nilphamari Sadar was 3.25% and 4.10% in Sayedpur, 4.82% in Domar, 5.86% in Dimla, 3.85% in Joldhaka and 4.70% in Kishoreganj. It was found that 58.84% filarial patients were male and 41.16% were female; highest prevalence of the disease was observed at the age group of 41 - 60 years. Illiteracy and poverty are the important social risk factors of this disease , about 45% patients were illiterate. Most of the infected patients were very poor and belong to low income group. Only 40.5% patients knew about filariasis. Only 26.1% patients used mosquito curtains. During the study period, it was found that 66.15% of hospitalized filarial patients were male and 33.85% were female, in the Filaria Hospital of Nilphamari. The highest outdoor patients in Nilphamari Hospital were of age group 40 - 59 years and 76.22% patients had hydrocele. Dhaka Univ. J. Biol. Sci. 25(2): 103-111, 2016 (July)